A Profile of Older Adults With a History of Stroke Receiving Home Care in Ontario, Canada. Issue 3 (August 2019) - Zoratti, Michael J.; Fisher, Kathryn; Guthrie, Dawn; Griffith, Lauren E.
The demand for home care services is increasing, yet the literature describing the clinical characteristics of community-dwelling individuals with a history of stroke who receive home care is limited. In this retrospective, cross-sectional, population-level study, data were sourced from home care recipients aged 65+ who had a routine assessment using the Resident Assessment Instrument for Home Care (RAI-HC) in Ontario between January 2007 and December 2011. The RAI-HC contains several health status indicators and validated health index scales. The association of a history of stroke on health status was assessed through a series of logistic regression models, adjusted for age, sex, and number of comorbidities. Sex differences were also explored. A change in odds of ≥25% was considered to indicate a clinically important finding. From the home care data ( N = 319, 694), 56, 909 individuals had a stroke diagnosis, with approximately 86% diagnosed with ≥3 chronic conditions. A stroke diagnosis was associated with a higher risk of limitations or impairments with communication, locomotion, continence, activities of daily living, and cognitive performance. A clinically meaningful difference was not observed for symptoms of depression. Few sex differences were observed. In an effort to support the development of effective home and community-based care programs, research is needed to understand differences in community-dwelling versus institutional populations. Community-dwelling individuals with a history of stroke show higher levels of impairment and limitations compared with those without, suggesting areas where home care resources could be improved to help manage the chronic effects of stroke.